The Effect of Financial Inclusion on Food Security: Evidence from Developing and Developed Countries - Yasmin, Yasmin; Setiastuti, Sekar Utami (Economics and Finance in Indonesia, 2023)
This study investigates the global impact of financial inclusion on food security, with a focus on both developing and developed countries. The study constructs a financial inclusion index using the Sarma method and secondary data sourced from IMF and World Bank databases. System GMM is employed as the estimation method due to its effectiveness in addressing endogeneity issues and its efficient and consistent use of instruments. The analysis reveals that financial inclusion has a positive and statistically significant effect on food security across all research sub-samples. In addition, the study incorporates interaction variables between financial inclusion and the COVID-19 pandemic to explore how the crisis alters the relationship between financial inclusion and food security. The findings indicate that the COVID-19 crisis has globally diminished food security and moderates the impact of financial inclusion on food security. Overall, the study confirms that financial inclusion is a crucial factor in enhancing food security worldwide, with no substantial disparity between developed and developing countries. Nevertheless, the global COVID-19 pandemic has demonstrated a capacity to weaken the beneficial effects of financial inclusion on food security.